Litigating Climate Claims in India - Shibani Ghosh (AJIL Unbound, 2020)
Jacqueline Peel and Jolene Lin's informative assessment of climate litigation in the Global South is a vital and timely contribution to the growing literature on the issue. It relies on a definition of climate litigation that allows the authors to draw on a much larger set of cases from the Global South by including cases in which climate concerns are “at the periphery.” This essay examines climate litigation in India. Although the term “global warming” started appearing in Indian environmental judgments in the 1990s, climate litigation in India is of relatively recent provenance, and with a few exceptions, climate concerns are peripheral to other, more mainstream environmental issues. Peel and Lin analyze five Indian cases as part of their Global South docket; I expand this set by including fourteen more cases that I believe fit their article's chosen definitional ambit. I classify these cases into four categories based on the use of climate language—reference to climate change, greenhouse gas (GHG) emissions, or the international negotiations—in the courts’ judgment. Drawing from case law analysis and Indian environmental litigation, I make observations about what we can interpret from the current set of climate cases, and I predict that while conditions are favorable for climate litigation in India to grow, in the near future climate claims are likely to remain peripheral issues.